Estoniaundersökningen 1994 - Göran Gustafsson (Swedish National Data Service, 1997)
The survey was conducted by SIFO on behalf of the Estonia group at the Swedish Church Research Secretariat in Uppsala. The study was conducted over a two week period about two months after the sinking of the ferry M/S Estonia on the 28th of September 1994. The ship was wrecked in a heavy storm during its journey from Tallinn, Estonia to Stockholm, Sweden. On board were 989 people, of which 852 lives were claimed.The accident is the largest ship disaster in peacetime in the Nordic seas of all time. After the sinking of the Estonia, a variety of efforts were made by various organizations, to help and assist in the difficult situation. The study was aimed to investigate what attitude the public had to the Church of Sweden after its response to the ferry disaster. Questions were asked about religious activity, sense of belonging to the Church of Sweden, altered perception of the Church of Sweden's role in society after the Estonia disaster, and religious activities as a result of the sinking of the Estonia. Respondents also had its approach to a number of statements about the religious dimensions of the Estonia disaster. Purpose: To investigate the public opinion's attitudes to the Church of Sweden after its response to the Estonia ferry disaster. Undersökningen har genomförts av SIFO på uppdrag av Estoniagruppen vid Svenska kyrkans Forskningssekretariat i Uppsala. Undersökningen gjordes under en tvåveckorsperiod cirka två månader efter färjan M/S Estonias förlisning den 28 september 1994. Fartyget gick under i svår storm under sin färd från estländska Tallinn till Stockholm. Ombord fanns 989 personer varav 852 förolyckades. Olyckan är den största fartygskatastrofen i fredstid i nordiska farvatten genom tiderna. Efter Estonias förlisning gjordes en mängd insatser från olika organisationer för att hjälpa och bistå i den svåra situationen. Undersökningens syfte var att se vilken attityd allmänheten hade till Svenska kyrkan efter dess insatser med anledning av färjekatastrofen. Frågor ställdes om kyrklig aktivitet, ...